The Trans Effect in Electrocatalytic CO2 Reduction: Mechanistic Studies of Asymmetric Ruthenium Pyridyl-Carbene Catalysts - Gonell, Sergio; Massey, Marsha D; Moseley, Ian P; Schauer, Cynthia K; Muckerman, James T; Miller, Alexander J. M (Journal of the American Chemical Society, 2019)
A comprehensive mechanistic study of electrocatalytic CO2 reduction by ruthenium 2,2′:6′,2″-terpyridine (tpy) pyridyl-carbene catalysts reveals the importance of stereochemical control to locate the strongly donating N-heterocyclic carbene ligand trans to the site of CO2 activation. Computational studies were undertaken to predict the most stable isomer for a range of reasonable intermediates in CO2 reduction, suggesting that the ligand trans to the reaction site plays a key role in dictating the energetic profile of the catalytic reaction. A new isomer of [Ru(tpy)(Mebim-py)(NCCH3)]2+ (Mebim-py is 1-methylbenzimidazol-2-ylidene-3-(2′-pyridine)) and both isomers of the catalytic intermediate [Ru(tpy)(Mebim-py)(CO)]2+ were synthesized and characterized. Experimental studies demonstrate that both isomeric precatalysts facilitate electroreduction of CO2 to CO in 95/5 MeCN/H2O with high activity and high selectivity. Cyclic voltammetry, infrared spectroelectrochemistry, and NMR spectroscopy studies provide a detailed mechanistic picture demonstrating an essential isomerization step in which the N-trans catalyst converts in situ to the C-trans variant. Insight into molecular electrocatalyst design principles emerge from this study. First, the use of an asymmetric ligand that places a strongly electron-donating ligand trans to the site of CO2 binding and activation is critical to high activity. Second, stereochemical control to maintain the desired isomer structure during catalysis is critical to performance. Finally, pairing the strongly donating pyridyl-carbene ligand with the redox-active tpy ligand proves to be useful in boosting activity without sacrificing overpotential. These design principles are considered in the context of surface-immobilized electrocatalysis.